Fuzzy service selection in a distributed object-oriented environment. - Bosc, P.
In network-centered execution environments, client objects can transparently invoke services offered by remote server objects, according to their published interface. The object selection problem requires the evaluation of the fitness of a pool of candidate server objects on the basis of the available information about their functional and nonfunctional features. Network-centered systems usually store such information in a trader agent that can be browsed or queried by client objects. In this paper, a fuzzy data model is proposed as the basis of the design of such a trader system, taking into account synergy between objects' features. Our trader is based on a fuzzy query algebra allowing for deriving operator definitions (therefore, query execution mechanisms) at run time, on the basis of user-selected semantics
Keywords: CORBA; Client server systems; Distributed systems; Fuzzy set theory; Intelligent trader system; Network-centered execution; Object-oriented systems; Query model; Server selection